Cattle Diseases Molecular and Biochemical Approach - Kükürt, Abdulsamed; Gelen, Volkan (Veterinary Medicine and Science, 2023)
Cattle Diseases - Molecular and Biochemical Approach is a vital reference for anyone working in the field of animal health and welfare, including veterinarians, researchers, and students. This comprehensive book offers insights into the molecular and biochemical mechanisms underlying various cattle diseases and provides practical guidance for improving animal health and productivity. The contributions from leading experts in the field cover a range of topics, including lumpy skin disease, zoonotic diseases, acute phase proteins, hepatic injury, paraoxonase 1, and sustainable livestock practices. Whether you are a practicing veterinarian or a researcher, this book is an important resource for expanding your knowledge in the field of cattle diseases and their molecular and biochemical mechanisms.